PENENTUAN KUALITAS LEMAK PADA BAGIAN PERUT IKAN PATIN DJAMBAL (Pangasius djambal) - Hamsinah -; Alimuddin -; Erwin - (PROSIDING SEMINAR KIMIA, 2013)
The purpose of this research was to determine the quality of fat in the abdomen djambal patin fish, which includes parameters water content, free fatty acid, iodine number, peroxide number, and the physical characteristics of the fat which includes the melting and freezing. Each parameter in each sample were given treatment three replications. The method used to determine water content, free fatty acid, iodine number, peroxide number is method Open oven, alkalimetri titration and iodometric titration.The results for water content, free fatty acid, peroxide number and iodine number in each sample from the average of three repetitions was 4.4%, 0.0563%, 11.52 meq and 8.34. Based on these results it can be concluded that the water content and the peroxide number weren’t conform in Indonesian national standards, while the free fatty acid content and iodine number were conform in Indonesian national standards.